RANCANGAN USER CENTERED DESIGN DALAM PENGEMBANGAN WEBSITE SEMINAR - Zahrach Artamevia; Agung Triayudi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
Seminar is one of the activities to get knowledge from someone who is an expert in his field, therefore many people who enthusiastically participate in seminar activities. The National University Biology Association is still conducting conventional transactions where participants come to the committee to buy tickets and also the committee recording seminar participants manually. The purpose of this study was to design a seminar ticket booking system using the User Centered Design (UCD) method so that it could easily make the seminar participants in ordering tickets and also facilitating the committee so they would no longer record data from the seminar participants manually. This website is designed using the programming language used in the design of the website for displays is PHP and MySQL as storage media. User Centered Design (UCD) focuses on user requirements. This research produces an easy-use system, where participants can register if they do not have an account, login, and can make a seminar ticket booking transaction. And from the admin side, the admin can delete event data, add event data and edit data events.